The penelope code system. Specific features and recent improvements - Salvat, Francesc (Annals of nuclear energy, 2015)
•penelope implements state-of-the-art models for electron and photon interactions.•It is characterized by a systematic use of class-II tracking of charged particles.•The code includes elaborate variance reduction methods and flexible geometry tools. Since its first release, back in 1996, the Monte Carlo code system penelope has evolved into both a flexible and reliable tool for describing coupled electron–photon transport in complex material structures. The present article contains an overview of the physical interaction models, particle tracking methods, geometry tools, and variance-reduction techniques implemented in penelope. Recent refinements aimed at improving the accuracy of the code, and its stability under variations of user-defined simulation parameters, are also described. These include the use of reliable cross sections for the ionization of inner atomic electron shells by electron/positron impact, a reformulation of the random-hinge method, and the use of fuzzy quadric surfaces in the description of the geometry.